2010
DOI: 10.1590/s1517-83822010000400016
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and cytotoxicity of seafood borne Aeromonas hydrophila

Abstract: The present study was conducted to determine the virulence and cytotoxicity of Aeromonas hydrophila strains isolated from seafood samples collected from 5 major fish markets in Chennai, Tamil Nadu, India. Among 73 A. hydrophila strains isolated from fish and shrimp samples, 86.3% exhibited haemolysis, 78.1% produced slime, 98.63% produced protease and also demonstrated cytotoxicity on Vero cells. Cell shrinkage, detachment and rounding of Vero cells were recorded as cytotoxic changes. Only one strain did not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…The prevalence of cytolytic enterotoxin gene carrying A. hydrophila isolates reported in our study are comparable with those reported from Malaysia [9,13] . However, our results are higher than the results of a study conducted in India [27] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of cytolytic enterotoxin gene carrying A. hydrophila isolates reported in our study are comparable with those reported from Malaysia [9,13] . However, our results are higher than the results of a study conducted in India [27] .…”
Section: Discussionsupporting
confidence: 89%
“…Also several investigations have shown that members of the genus Aeromonas are also widely distributed in various foods such as meat [9,10] , sea food [11][12][13][14] , and vegetable [15] . Thus, foods have been suggested as a vector in the dissemination of this pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos demonstram que A. hydrophila possui vários fatores de virulência, citotoxinas e enzimas extracelulares com atividade proteolítica e hemolítica, importantes para o desenvolvimento da patogênese. Produzem também substâncias glicoconjugadas que auxiliam na formação de biofilme 10 , o qual impede a ação dos medicamentos no tecido lesionado, levando à falha no tratamento antimicrobiano 4,11 .…”
Section: Discussionunclassified
“…It is pathogenic to shrimps, frogs, and fishes (Martin-Carnahan and Joseph, 2005;EPA, 2006). The infection caused by this bacterium can lead to significant mortality rates within a short period, causing losses to fish and shrimp breeders (Illanchezian et al, 2010;Mangunwardoyo et al, 2010). The disease symptoms vary, but infected fish generally show skin ulcers and haemorrhaging in the skin, gills, and oral cavity (Gardenia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%